Pengaruh Sarana Prasarana terhadap Hasil Belajar Siswa Teknik Instalasi Tenaga Listrik di Sekolah Menengah Kejuruan - Harahap, Khoiruddin Saleh; Sukardi, Sukardi (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2024)
This research aims to determine the extent of the influence of practicum infrastructure on the learning outcomes of class XI Electrical Installation Engineering students at SMK Negeri 2 Panyabungan in the electrical lighting practicum subject. This type of research uses quantitative methodology and has three stages in its research design: preparation, implementation, and conclusion. Documentation and questionnaires were used to collect data. Use reliability and validity tests to evaluate research instruments. Prerequisite tests, analysis, and hypothesis testing were carried out on the data. Based on the research results, the infrastructure of SMK N 2 Panyabungan is of high value and is included in the facilities group. The results of the data analysis show that the infrastructure of SMK N 2 Panyabungan is in good condition. The average score for the learning outcomes of class XI TITL SMK N 2 Panyabungan students is classified as very high and includes very good scores. The infrastructure (x) variables and student learning outcomes (y) in class XI TITL SMK N 2 Panyabungan have a positive and substantial relationship. The regression line equation is used to explain test findings in data analysis which show that infrastructure can have an influence.